DIGITAL BRANDING STRATEGY IN THE INSTAGRAM CONTENT OF THE STATISTICS INDONESIA (BPS) SOUTH SULAWESI PROVINCE - Salam, Erick; Razak, Mashur; Daga, Rosnaini (International Journal of Multidisciplinary Research and Literature, 2025)
This study aims to analyze the digital branding strategy implemented by the Statistics Indonesia (BPS) of South Sulawesi Province through its Instagram content. In the digital era, social media has become a crucial communication tool for government institutions to build their image and gain public trust. This research adopts a descriptive qualitative method with data triangulation through interviews, documentation, and observation. The findings reveal that BPS South Sulawesi actively utilizes Instagram by delivering informative, educational, and interactive visual content. The branding strategy includes presenting statistical data via infographics, using accessible language, and fostering two-way engagement with the public. Despite its effectiveness in disseminating information, there are still areas for improvement, such as content consistency, creative execution, and strengthening visual identity. This study recommends optimizing Instagram features and enhancing the role of public relations in building the institution's credibility.